Identification of Community-Dwelling Older Adults With Shoulder Dysfunction: A Pilot Study to Evaluate the Disabilities of the Arm, Shoulder and Hand Survey. (17th September 2022) - Davis, Derik L.; Almardawi, Ranyah; Terrin, Michael L.
Introduction: The Disabilities of the Arm, Shoulder and Hand (DASH) survey estimates the upper limbs' dysfunction in one score, but limited evidence exists to justify use of DASH to screen older adults for shoulder dysfunction at routine health maintenance primary care visits. We sought (1) to determine if the DASH, American Shoulder and Elbow Surgeons (ASES) and Simple Shoulder Test (SST) surveys are related to one another and (2) to determine the relationship of DASH, ASES and SST scores with 36-Item Short Form (SF-36) subscales, shoulder forward flexion range of motion (FF-ROM) and abduction (ABD-ROM) in older adults. Methods: Prospective pilot study of 23 community-dwelling adult volunteers [mean age (± standard deviation), 69.3 ± 6.7 years; range, 61-84 years, with no rotator cuff repair or joint replacement. Shoulder MRI, ROM testing, DASH, ASES, SST, SF-36, Katz activities of daily living (ADLs), and Lawton-Brody instrumental ADLs (IADLs) were completed at one time point. Descriptive and correlation analyses were performed. Results: Means: DASH, 17.4 ± 19.5; ASES, 81.3 ± 19.7; SST, 71.7 ± 28.5; Katz ADLs, 5.9 ± .3; Lawton-Brody IADLs, 8.0 ± .0; FF-ROM, 140.2° ± 31.5°; and ABD-ROM, 128.3° ± 31.9°. Nearly 48% had supraspinatus tendon tear. Correlation among DASH, ASES, and SST was strong (|rho ≥.88|; P < .001). DASH, ASES, and SST had strong correlation (|rho ≥.71|; P < .001) with shoulder FF-ROM and ABD-ROM. DASH had near equivalent or slightly stronger correlation for all SF-36 subscales relative to ASES and SST. DASH showed strong or moderate correlation ( P < .05) to most SF-36 subscales. Conclusion: DASH, ASES and SST strongly correlated with one another. DASH, relative to ASES and SST, has similar correlation to shoulder FF-ROM, ABD-ROM and SF-36 subscales in older adults. Our pilot study suggests that the DASH survey has potential utility to identify occult shoulder dysfunction in community-dwelling older adults who have normal Katz ADLs and Lawton-Brody IADLs if administered during routine health maintenance primary care visits.